A Comparative Analysis of Speech Production in Male and Female Broca’s Aphasia Survivors - Dwi Aryani Salsabila Zaqiyyah; Lusiana Suciati Dewi (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2026)
This study aims to analyze the characteristics of speech production and communication strategies in two Broca’s aphasia survivors of different genders, Sarah Scott and Mike Caputo. This research employs a qualitative method with a comparative descriptive approach. Data were obtained from two YouTube videos uploaded in 2017 and analyzed through a process of observation, transcription, identification, and interpretation of linguistic data. The study focuses on speech production characteristics such as non-fluent speech, telegraphic speech, disfluency, pauses, hesitation, and word-finding difficulties, as well as the communication strategies employed by both subjects to maintain social interaction post-stroke. The results indicate that both subjects exhibit the core characteristics of Broca’s aphasia, manifested as non-fluent speech, simplified sentences, and word-finding difficulties. However, discrepancies emerge regarding their levels of communicative fluency and the strategies utilized. Sarah Scott demonstrates a more independent communication pattern through the use of gestures, self-repair, repetition, and active communication practice within an aphasia community. Conversely, Mike Caputo relies more heavily on his wife's assistance to co-construct communication. This study demonstrates that the communicative recovery process in Broca’s aphasia patients is modulated by neurological factors, social support, communication practice, and the social environment. This research proves that social media platforms like YouTube can serve as valuable sources of authentic data in neurolinguistic studies.